2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2019v18n3/lujan
|View full text |Cite
|
Sign up to set email alerts
|

MICROENCAPSULATION OF MICROBIAL CONSORTIUM AND VOLATILE COMPOUNDS OF PALM (Acrocomia aculeata) WINE

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…In relation to the morphology of the microcapsules, similar results were reported by Luján-Hidalgo et al [44] for the encapsulation of a microbial consortium using maltodextrin, gum Arabic, xanthan gum and sodium alginate as coating materials and Loksuwan [45] for the encapsulation of β-carotene with modified tapioca starch, native tapioca starch and maltodextrin as encapsulant agents. This morphology and structure of powders have been reported previously and could be explained by the faster volatilization of the water during drying [46].…”
Section: Discussionsupporting
confidence: 80%
“…In relation to the morphology of the microcapsules, similar results were reported by Luján-Hidalgo et al [44] for the encapsulation of a microbial consortium using maltodextrin, gum Arabic, xanthan gum and sodium alginate as coating materials and Loksuwan [45] for the encapsulation of β-carotene with modified tapioca starch, native tapioca starch and maltodextrin as encapsulant agents. This morphology and structure of powders have been reported previously and could be explained by the faster volatilization of the water during drying [46].…”
Section: Discussionsupporting
confidence: 80%
“…The sap is fermented naturally, without the producers adding any inoculum, carrying out acidic, alcoholic and sometimes acetic fermentations, which gives the drink its characteristic flavor. The sweet taste of the sap produced in the 1st days of collection is due to the presence of sucrose and other sugars, as indicated by Luján-Hidalgo et al (2019), who reported a concentration of 110 g/L of sucrose, as well as 48 and 51 g/L of glucose and fructose; respectively, and its decrease with the passing of the days explains the change of flavor to one of alcoholic taste, due to the fact that these sugars are used by the developed native microbiota; transforming them into a mixture of compounds, among which are mainly ethanol, whose concentration can reach 4.7-10.31% w/v, depending on the environmental conditions and the time of collection of the drink (Santiago-Urbina et al, 2013;Coutiño et al, 2015Coutiño et al, , 2020. Regarding the use of the taberna as a remedy for some gastrointestinal diseases; Romero-Luna et al (2017) pointed out that the taberna, among other traditional drinks, contain beneficial microorganisms for health, since they improve the balance of the intestinal flora, thereby reducing the risk of gastrointestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of the taberna as a remedy for some gastrointestinal diseases; Romero-Luna et al (2017) pointed out that the taberna, among other traditional drinks, contain beneficial microorganisms for health, since they improve the balance of the intestinal flora, thereby reducing the risk of gastrointestinal diseases. In studies carried out in taberna, an autochthonous microbiota composed of lactic and acetic bacteria and yeasts has been found (Alcántara- Hernández et al, 2010;Santiago-Urbina et al, 2013, 2015Luján-Hidalgo et al, 2019), which possibly confer probiotic potential to the beverage, as pointed out by Coutiño et al (2020), who also point out that the taberna contains bioactive compounds, such as phenolic compounds, vitamins, short-chain fatty acids, among others; that can be generated by the microbiota developed during the fermentation of the sap, or come directly from the plant. Regarding the custom of attaching a red ribbon to the stems, Zuart-Macías et al (2013) also describe this practice, to avoid excessive and sudden acidification of the taberna, caused by the admiration of people who are not familiar with it, even commenting that some producers prevent the passage of strangers to the place where the stems of the palms in production are located.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method to determine glass transition is the differential scanning calorimetry (DSC), which detects the change in heat capacity occurring over the transition temperature range. In order to reduce stickiness, the glass transition temperature of the juice powder can be increased with the addition of maltodextrin 11 . The Tg of an amorphous or semi-crystalline polymer is inferior to its melting point, it is important to differentiate between these two temperatures that describe a phase change.…”
Section: Introductionmentioning
confidence: 99%